Development of Geogebra Assisted Mathematics Learning Devices on Two-Variable Linear Programming Material - Yenny Farida Br Ginting; Mangaratua M. Simanjorang (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the validity and practicality of learning geogebra-assisted mathematics developed on linear programming material. The development model used is the Analysis, Design, Development, Implementation and Evaluation (ADDIE) model. This research was conducted at Juhar 1 Public High School located in Juhar Village, Juhar District, Karo Regency. The subjects of this study were students of class XI IPA-1 at SMA Negeri 1 Juhar in the odd semester of the 2020/2021 academic year. The results showed that the validity of the GeoGebra-assisted mathematics learning tool on two-variable linear program material was included in the very valid category. In the practicality of learning tools, it is obtained that the average percentage of the implementation of learning in class is 84.44% with a good category. And the results of student responses to LAS that have been developed obtained a percentage of 84.85% with a very practical category, it can be concluded that the learning tools developed are practical.